Developing Materials Of English Textbook "When English Rings The Bell" For The Seventh Grade Of Junior High School Based On Process Standard Of Curriculum 2013 - SUSANTI, Indah, Prof. Dr. Endang Fauziati, M. Hum, Mauly Halwat Hikmat, Ph. D (2015)
This research is mainly intended to develop materials of English textbook "When English Rings the Bell" for the seventh grade of junior high school based on process standard of curriculum 2013. The objectives of this research are to develop the material for observing, questioning, experimenting / exploring, associating, and communicating activities. This research is qualitative research which involves simple research and development approach. The object of this research is English textbook named "When English Rings the Bell" written and published by The Ministry of Education and Culture in 2013. The writer analyzes the textbook of seventh grade students including the material used in the first and second chapter. In collecting the data, the writer uses documentation method. In analyzing the data, the researcher does some steps which involves presenting the data, classifying the data, describing the data, making conclusion, and drawing pedagogical implication are used to analyze the data. This research describes some cases which should be done by the teachers in developing the materials of English textbook. They are analyzing the book in order to decide the chapter will be developed, arranging the guidelines for the proposed supplementary material development, and developing proposed supplementary material development. The findings show that the materials in the first two chapters have been developed by the researcher in five stages of scientific approach. They are materials for observing, questioning, experimenting, associating, and communicating activities. For each stage, the materials are developed through some steps, i.e. deciding the skill to develop, arranging classroom activities, and also completing the classroom activities by giving the guidelines to be used in teaching learning process.